Analyses of Pre-Service Teachers’ Errors in Solving Algebraic Tasks in Ghana. - Oppong, Richard Asumadu; Adjei, Emmanuel Antwi; Amoah, Emmanuel Kojo; Okuleteh, Enock; Larri, Baba (EDUPEDIA Publisher, 2024)
This study analyzed prospective basic education teachers’ errors in solving algebraic tasks using Newman’s Error Analysis (NEA). The study employed an interpretivist philosophical paradigm with a qualitative case study design. Data were collected from 250 prospective mathematics teachers randomly selected from four colleges of education in the eastern region of Ghana using super item tests and unstructured interview protocols. Thematic analysis was employed to analyze the qualitative data. The study findings revealed that transformation and encoding errors among prospective mathematics teachers are the most prevalent errors. Other error types encountered included comprehension errors and process skills errors. In order to reduce aspiring mathematics teachers’ errors, the study emphasizes the necessity of focused interventions and professional development programs to address transformation and comprehension errors in algebraic concepts.